Carbon dioxide laser treatment of penile intraepithelial neoplasia. Issue 6 (December 2017) - Zreik, Abdullah; Rewhorn, Matthew; Vint, Ross; Khan, Rehan; Hendry, David
Abstract: Introduction & objective: The non-invasive nature of penile intraepithelial neoplasia (PeIN) allows for curative penile sparing therapy and is recommended, in their guidelines, by the European Association of Urology (EAU). Treatment options include topical chemotherapy, immunotherapy, laser treatment, photodynamic therapy and surgical excision. Our primary aim was to evaluate the outcome of carbon dioxide (CO2 ) laser treatment of penile intraepithelial neoplasia. Methods: A retrospective review of 47 patients who underwent CO2 laser ablation of PeIN, from May 2008 to June 2015, in our tertiary referral centre was performed. All patients underwent acetic acid mapping and had their lesions ablated with a Lumenis Shaplan CO2 laser device. Patients had regular follow up and further suspicious areas underwent re-biopsy. Results: Forty-seven men had primary PeIN. After laser treatment, 8 men (17%) had a recurrence and the average time to recurrence was 19.4 months. Seven of the eight patients with recurrences, pathologically had further PeIN and one patient developed G1 pT1 disease. These patients underwent further laser treatment, glans resurfacing or local excision. No patients required penectomy. The average length of follow-up was 29 months (rg: 1–76). Penile cancer-specific survival was 100% and overall survival 98%. No patients required re-admission or developed other long-term complications, such as meatal stenosis from their treatment. Conclusion: Carbon dioxide laser treatment for penile intra-epithelial neoplasia is effective due to its 100% response rate, low progression rate and lower recurrence rate compared with topical agents. The laser has minimal morbidity with cosmetically acceptable outcomes compared to more invasive resurfacing surgeries.